DIALLEL CROSSES AND SDS-PAGE PROFILING FOR UNDERSTANDING GENETIC COMPATIBILITY IN SUNFLOWER (HELIANTHUS ANNUUS L.) - LAIQUE, A; MUSTAFA, HSB; TANVEER, M; ATHAR, MH; HASSAN, M; SARWAR, S; SHAHZAD, S; ASGHAR, S; QAMAR, R; KHAN, QAT; ALTAF, M; IQBAL, MA (Biological and Clinical Sciences Research Journal, 2024)
Sunflower (Helianthus annuus L.) is an economically significant oilseed crop cultivated globally, including Pakistan, due to its versatile applications in the food, feed, and oil industries. Various sunflower accessions were crossbred using a diallel technique. Following the harvest of the first season crop, these seeds were cultivated in a Randomized Complete Block Design (RCBD) with three replications in the spring of 2022–2023 for further evaluation. Data was collected on plant height, head diameter, leaf area, number of leaves per plant, internodal distance, stem diameter, head diameter, oil content, and protein content. SDS-PAGE was utilized to analyze the data using the 4×4 Griffing’s technique for full diallel and to assess genetic diversity among superior crossings. The crosses F-44×F-58, F-48×F-58, F-44×F-58, and F-48×F-54 were identified as the best specific combiners due to their high SCA effect. Additionally, F-44×F-48, F-48×F-58, F-54×F-58, and F-44×F-54 demonstrated high RCA effect. Moreover, F-44×F-48, F-44×F-54, F-44×F-58, and F-58×F-44 exhibited significantly better or mid-parent heterosis. Gene action analysis revealed that plant height and internodal length were governed by additive gene action, while other traits showed dominant gene action. For advanced investigations, proteomic analysis of the genotypes was conducted, revealing variability among the genotypes for multiple traits. The standard SDS-PAGE protocol was followed, using a 15% resolving gel and a 10% stacking gel. Protein analysis PCR was conducted at a constant voltage of 80 volts for two hours, with F-48 showing the most optimal amplification. F-48 and P-58 emerged as the superior performers and best combiners.